Spindle cell hemangioma of the spleen: A case report. Issue 9 (March 2019) - Gao, Bing-Qiang; Zhou, Dong-Kai; Qian, Xiao-Hui; Zhang, Wang; Ying, Li-Xiong; Wang, Wei-Lin
Abstract: Rationale: Spindle cell hemangioma (SCH) is considered a benign vascular lesion. It typically develops as a solitary nodule or multiple masses located in the dermal or subcutaneous layers of the distal extremities. To the best of our knowledge, there are no prior reports of SCH in the spleen. Patient concerns: A 41-year-old male was admitted to our hospital with recurrent headaches, nausea, and vomiting persisting for 5 days. Ultrasound, computed tomography, and magnetic resonance imaging revealed multiple space-occupying lesions in the spleen, and the biggest lesion was 4.8 cm × 5.4 cm in size. Interventions: The patient underwent laparoscopic splenectomy. Diagnosis: A diagnosis of spindle cell hemangioma of the spleen was made based on the histopathology. Outcomes: No evidence of local recurrence or distant metastases was observed over 4-year follow-up. Lessons: Splenic SCH may exhibit relatively high proliferative activity and be comorbid with epithelioid hemangioendothelioma or angiosarcoma, raising the possibility of malignant potential. However, the patient remained alive and disease-free 4 years after the operation. The nature of SCH in deep soft tissues requires further study.